Distributed Denial of Service Attack and Defense - Yu, Shui.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This brief provides readers a complete and self-contained resource for information about DDoS attacks and how to defend against them. It presents the latest developments in this increasingly crucial field along with background context and survey material. The book also supplies an overview of DDoS attack issues, DDoS attack detection methods, DDoS attack source traceback, and details on how hackers organize DDoS attacks. The author concludes with future directions of the field, including the impact of DDoS attacks on cloud computing and cloud technology. The concise yet comprehensive nature of this brief makes it an ideal reference for researchers and professionals studying DDoS attacks. It is also a useful resource for graduate students interested in cyberterrorism and networking.
An Overview of DDoS Attacks -- Malicious Networks for DDoS Attacks -- DDoS Attack Detection -- Attack Source Traceback -- DDoS Attack and Defence in Cloud -- Future Work.
Keywords: Computer science; Computer Communication Networks; Data protection; Information systems; Computer Science; Systems and Data Security; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Systems and Communication Service